TEACHING AIDS FOR THE TEACHING OF TECHNICAL GRAPHICS - HODIS, Zdenek; VYBIRAL, Petr; HRBACEK, Jiri; VINKLOVA, Sylva (Trends in education, 2015)
This contribution is focused on problem of educational aids and instruments used in subjects of technical graphics and design. Commercial teaching aids are compared with original solutions designed for practice to the first-angle projection. The contribution describes the work methodology with teaching aids (display area) and the attitudes of students and pupils.
Keywords: Technical drawing; first-angle projection; design; didactic technology